A COMPARATIVE STUDY OF THE IMPLEMENTATION OF DEEP LEARNING IN INDONESIA AND MALAYSIA BASED ON BIGGS AND TANG'S THEORY - Ahmad As'ari; Sudrajat Sudrajat; Raras Gistha Rosadi (Indonesian Journal of Social Science Education (IJSSE), 2026)
This study aims to analyze and compare the implementation of deep learning in Indonesia and Higher Order Thinking Skills (HOTS) in Malaysia using the constructive alignment framework proposed by Biggs and Tang. This research employs a qualitative approach with a comparative study design through literature review. The data sources include official curriculum documents as well as relevant academic journals and literature. Data analysis was conducted using content analysis by examining the alignment between learning objectives, learning activities, and assessment. The findings indicate that Indonesia implements deep learning through the Merdeka Curriculum with a mindful, meaningful, and joyful approach, while Malaysia integrates HOTS systematically through the Malaysia Education Blueprint (PPPM) 2013–2025. Both countries share similar goals in developing 21st-century skills, but differ in terms of implementation and consistency. Malaysia demonstrates a higher level of alignment, whereas Indonesia is still in a transitional phase with several challenges. Therefore, strengthening constructive alignment through teacher capacity building, instructional design development, and assessment reform is necessary.